Preparation and Evaluation of Extended Release Matrix Tablet of Salbutamol Sulphate - Yadav, Ajeet; Gupta, Naveen; Rajput, Dharmendra Singh (Asian Journal of Pharmaceutical Research and Development, 2024)
The purpose of this research was to see how the physicochemical properties and porosity of matrix tablets containing various types of natural polymers affected the release of salbutamol sulphate. The sustained drug delivery systems are designed to achieve a constant release of drug from the formulation. The therapeutic levels are adequately maintained throughout the dosing interval. Moreover, the constant rate of absorption also reduces the dosing frequency and thus improves patient compliance. Natural polymer obtained from the gummy exudates and plant fibers. Various natural polymers in use are xanthan gum, acacia, guar gum, agar, carrageenan, chitosan gelatin, etc. With the advancements in technology and insutrial products, natural polymer manufacturing industry has come a long way. India has been serving the polymer producing industry since a long time. Salbutamol sulphate released in a controlled manner to a patient needing this therapy, thereby resulting in a better patient compliance. Accordingly, this study was designed to enhance the bioavailability of drug by prolonging its duration in the stomach as matrix type dosage forms with controlled release. Extended release matrix tablets of salbutamol sulphate were prepared by the direct compression method, using locust bean gum and HPMC K 15M as polymers. The effect of the nature of polymers was studied by preparing various formulations of extended release matrix mucoadhesion tablets.